Digital Transformation in Higher Education System: Learning Technologies at Open University of Mataram - Sun Yanna; Mohamad Mustari; Asrin (International Journal of Scientific Multidisciplinary Research, 2024)
The proliferation of technology has significantly impacted learning development. This study aimed to investigate the effectiveness of learning technologies based on students’ perspectives and to discover the challenges encountered when using technologies. In conducting a qualitative case study, the researcher collected data using an open-ended questionnaire at the Open University of Mataram. The data from six informants were analyzed by using the thematic analysis technique. The analysis procedures were based on Kawulich's (2004), which encompassed narrative, coding, interpretation, confirmation, and presentation. The result showed that the students found technology in their learning was effective primarily in creating attractive, practical, and accessible learning experiences, promoting flexible learning and independent learners, and enriching and deepening understanding. Meanwhile, three main challenges were identified: an unstable network, social media, environmental distraction, and a lack of technological competence among students. This study recommends researching teachers’ perspectives on digital transformation for further studies